2020
DOI: 10.6018/analesbio.42.02
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral asymmetry in the mass and size of otolith of two cichlid species collected from Lake Ahémé and Porto-Novo Lagoon (Bénin, West Africa)

Abstract: Asimetría bilateral en la masa y el tamaño de otolitos de dos especies de cíclidos capturados en el lago Ahémé y la laguna de Porto Novo (Benín, África Occidental) Se estudia la asimetría de la masa del otolito sacular en dos especies de peces cíclidos Sarotherodon melanotheron y Coptodon guineensis recolectadas del lago Ahémé y la laguna Porto-Novo, Benín, África occidental. La longitud y el ancho de los otolitos de especímenes adultos de ambas especies se usaron para calcular la asimetría fluctuante en estos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Jawad (2012) mentioned that the level of asymmetry in the otolith width is the highest among the length and width values of Lutjanus bengalensis collected from the Muscat coast on the sea of Oman, with a trend towards increasing asymmetry in the length and width as the fish increases in length, adding that this asymmetry is attributed to the various pollutants present in the area. Similarly Jawad (2012) and Jawad et al (2012a) in Sardinella sindensis and Sillago sihama collected from the Persian Gulf near Bandar Abbas and Jawad et al (2020) in Sarotherodon melanotheron and Coptodon guineensis examined from Lake Ahémé and Porto-Novo Lagoon, Bénin, found the same results, except that a trend of increase in the value of asymmetry with fish length has been observed in the otolith width only. However, Al-Busaidi et al (2017) reported that both the length and width measurements of the otolith estimated from L. ehrenbergii in the Sea of Oman at Muscat City are good indicators for fish length and there is symmetry between the left and right otoliths.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Jawad (2012) mentioned that the level of asymmetry in the otolith width is the highest among the length and width values of Lutjanus bengalensis collected from the Muscat coast on the sea of Oman, with a trend towards increasing asymmetry in the length and width as the fish increases in length, adding that this asymmetry is attributed to the various pollutants present in the area. Similarly Jawad (2012) and Jawad et al (2012a) in Sardinella sindensis and Sillago sihama collected from the Persian Gulf near Bandar Abbas and Jawad et al (2020) in Sarotherodon melanotheron and Coptodon guineensis examined from Lake Ahémé and Porto-Novo Lagoon, Bénin, found the same results, except that a trend of increase in the value of asymmetry with fish length has been observed in the otolith width only. However, Al-Busaidi et al (2017) reported that both the length and width measurements of the otolith estimated from L. ehrenbergii in the Sea of Oman at Muscat City are good indicators for fish length and there is symmetry between the left and right otoliths.…”
Section: Discussionmentioning
confidence: 61%
“…During the last decades, study of the morphological characteristics of otoliths, in particular their shape, length, width, area, thickness and weight, has been used to test both genetic and environmental stressors and as a bioindicator to test the differentiation of populations and the variance in stock discrimination studies using Elliptical Fourier analysis (EFA) (Valentine et al, 1973;Campana & Casselman, 1993;Begg & Waldman, 1999;Torres et al, 2000;Smith et al, 2002;Panfili et al, 2005;Turan, 2006;Jawad et al, 2010Jawad et al, , 2011Jawad et al, , 2012aJawad et al, , 2012bJawad et al, , 2012cJawad et al, , 2016Jawad et al, , 2020Vignon & Morat, 2010;Cañás et al, 2012;Jawad, 2012Jawad, , 2013Lord et al, 2012;Treinen-Crespo et al, 2012;Mahe et al, 2014;Trojette et al, 2014Trojette et al, , 2015Abu El-Regal et al, 2016;Brophy et al, 2016;Hüssy et al, 2016;Rebaya et al, 2016Rebaya et al, , 2017Al-Busaidi et al, 2017;Fatnassi et al, 2017;Ider et al, 2017;Khedher et al, 2017;Rodgveller et al, 2017;Chakour & Elouizgani, 2018;Khemiri et al, 2018;Kontaş et al, 2018;Mejri et al, 2018;Wang et al, 2018;…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, the anatomy of the otolith has been shown to play an important role in discriminating the stock based on the life traits of individuals with the evolution of the habitat (Arai et al 2007). Studies of morphological variability in the otolith shape, structure, and development have shown that the otolith shape is species-specific and is influenced by ontogenetic, genetic, and environmental factors (Fashandi et al 2019), as well as by sex, growth, maturity, and pattern of fishery exploitation (Begg and Brown 2000), or by individual characteristics, e.g., the individual genotype (Jawad et al 2020) or the physiological state (Campana and Neilson 1985). But the possible cause of the intra-individual variation, particularly the asymmetry in shape between the right and left otoliths, has been poorly studied (Mille et al 2015).…”
Section: Introductionmentioning
confidence: 99%